2006
DOI: 10.4161/cbt.5.4.2478
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies of bismuth-213 labeled plasminogen activator inhibitor type 2 (PAI2) in a prostate cancer nude mouse xenograft model

Abstract: Objectives. The key objective of the study was to determine the single and multiple dose toxicity and efficacy of Bismuth-213 labeled PAI2 based targeted alpha therapy by selectively targeting uPA and uPAR in regressing prostate cancer in a nude mouse model. Targeted alpha therapy (TAT) is an experimental therapeutic modality for cancer. Another objective was to compare the in vivo pharmacokinetics using two different chelators to form the radioisotope-protein construct.Methods. The single and multiple intra-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Mice. This study is an extension of the previously published study, 27 which showed the MTD to be more than 1420 MBq/kg up to 13 weeks using weight loss as the indicator for toxicity. Biochemistry, haematology and histopathology of the specimens were carried out at 13 weeks, in addition to the monitoring weight loss to investigate subclinical abnormalities.…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…Mice. This study is an extension of the previously published study, 27 which showed the MTD to be more than 1420 MBq/kg up to 13 weeks using weight loss as the indicator for toxicity. Biochemistry, haematology and histopathology of the specimens were carried out at 13 weeks, in addition to the monitoring weight loss to investigate subclinical abnormalities.…”
Section: Methodsmentioning
confidence: 67%
“…Rabbits that received the lowest dose of 60 MBq/kg experienced weight gain similar to the controls, whereas weight gain was the slowest in the rabbits that received the highest dose of 350 MBq/kg. 27 Histopathology revealed that organs in all rabbits, except for the kidneys, were free of any radiation damage. The kidneys showed mild and patchy tubular necrosis at 60 and 120 MBq/kg, while at 350 MBq/kg, moderate to severe and widespread renal tubular necrosis with a compensatory expansion of interstitial tissue was observed.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The Balb/c nude mice were inoculated with 2 x 10 6 PC3 cells subcutaneously as per procedures published elsewhere. 13,19,31,32 Two different doses of cold bevacizumab (1 and Clinical Gastroenterology and Hepatolog 3 mg/kg) were administered twice weekly for three weeks. The control mice received saline injection in equal volume at each bevacizumab administration in test mice.…”
Section: Methodsmentioning
confidence: 99%
“…3 We have successfully prepared and tested labeled monoclonal antibodies and proteins in vitro and have demonstrated their efficacy for targeted alpha therapy (TAT) in vivo with various cancer models. [11][12][13][14][15][16][17][18][19][20][21] One of the labeled TAT products (antimelanoma monoclonal antibody 9.2.27 labeled with alpha emitting radionuclide Bismuth-213) has been successfully tested in our ongoing Phase I melanoma trials. [22][23][24] We have found partial to complete response in some patients without any signs of associated toxicity.…”
Section: Research Papermentioning
confidence: 99%